Preparation method and application of cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel

By using cellulose/phenolized lignin-Fe aerogel and BiOBr, the problem of difficult regeneration and degradation of existing solar interface evaporator materials is solved, low-cost, renewable, environmentally friendly solar seawater desalination and organic pollutant degradation are achieved, and water evaporation efficiency and photocatalytic performance are improved.

CN118725394BActive Publication Date: 2025-04-29NANJING FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410796492.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-04-29
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

The existing solar interface evaporator materials are difficult to regenerate and degrade, and have high costs, and the internal pore structure of biomass materials is difficult to regulate, resulting in low evaporation rate and the inability to effectively treat organic pollutants in sewage or industrial wastewater.

Method used

Cellulose/phenylated lignin-Fe aerogel and its composite bifunctional aerogel are used to combine phenylated lignin-Fe with BiOBr for solar seawater desalination and organic pollutant degradation. The aerogel is prepared by directional freezing and vacuum drying to form a material with a porous structure and high hydrophilicity.

Benefits of technology

Low-cost, renewable, environmentally friendly solar seawater desalination and organic pollutant degradation are achieved, and the three-dimensional network structure of aerogels improves water evaporation efficiency and photocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118725394B_ABST
    Figure CN118725394B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer composite materials, in particular to a cellulose / phenolic lignin-Fe aerogel and a preparation method and application thereof. The following scheme is now proposed, which includes dispersing phenolic lignin-Fe in a TEMPO oxidized cellulose nanofiber suspension to obtain a mixed solution, freezing it under liquid nitrogen conditions, and vacuum drying it to achieve a directional growth pore structure. By changing the content of phenolic lignin-Fe, the pore size of the aerogel is regulated to achieve a higher water evaporation rate. In addition, the phenolic lignin-Fe is compounded with BiOBr to obtain a photocatalyst BiOBr-phenolic lignin-Fe, which is added to the aerogel to obtain a cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel, which has the effect of photocatalytically degrading dyes. The preparation method of the present invention makes full use of the structural uniqueness of biomass lignin to obtain a bifunctional aerogel that can efficiently desalinate seawater while achieving photocatalytic degradation of dyes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer composite materials, and in particular relates to a preparation method and application of a cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel. Background Art

[0002] Water is one of the most precious and irreplaceable natural resources on Earth. Although about 71% of the Earth's surface is covered by water, only 0.01% of fresh water is available to humans. It is predicted that by 2025, about two-thirds of the world's population will face the severe problem of water shortage. In recent years, researchers have been committed to desalinating resource-rich seawater to produce fresh drinking water. However, traditional industrial desalination technologies, including reverse osmosis, multi-effect distillation, and electrodialysis, usually require complex infrastructure, centralized installation, and high energy consumption, making them unsuitable for water-scarce and remote areas. Therefore, solar interfacial evaporation desalination technology has attracted widespread attention due to its advantages such as low cost, sustainability, environmental friendliness, and no geographical restrictions.

[0003] A typical solar-driven interfacial evaporator is mainly composed of a light absorption layer and a water transfer layer. The light absorption layer is mainly composed of photothermal materials. The photothermal materials need to have good solar light absorption rate and photothermal conversion efficiency, and the water transfer layer needs to have a suitable pore structure. In recent years, people have developed various photothermal materials with a wide range of solar spectrum absorption and high solar photothermal conversion efficiency, such as carbon materials, semiconductors, conjugated polymers, and plasma nanoparticles. The solar evaporator works by absorbing solar thermal radiation by the evaporation material, which locates the energy on the evaporation surface, thereby heating water molecules and promoting the uninterrupted generation of steam. This mechanism effectively reduces heat loss and greatly improves evaporation performance. However, these materials are difficult to regenerate and degrade, and are expensive. Most biomass material evaporators are difficult to regulate due to the difficulty in regulating the internal pore structure, and the photothermal conversion and water transfer performance cannot be balanced, and the evaporation rate is generally low. Therefore, it is of great significance to select low-cost, renewable lignin materials, and to achieve the regulation of the internal structure of the evaporator by changing the lignin content, so as to develop an evaporator that takes into account both photothermal conversion and water transfer efficiency, high evaporation rate, and strong salt resistance. In addition, since solar evaporators alone cannot effectively treat organic pollutants in sewage or industrial wastewater, we also combine solar desalination with photocatalytic degradation. The addition of photocatalysts produces active free radicals that can purify impurities such as organic dyes in seawater, and it is possible to purify wastewater through the solar light absorption device system at the same time.

[0004] Lignin is the most abundant naturally occurring aromatic polymer. The pulp and paper industry produces more than 50 million tons of lignin as a byproduct each year, however, less than 5% of industrial lignin is used as a value-added product, most of which is burned as low-quality fuel or directly discharged as a pollutant. It is reported that the strong conjugation and π-π stacking of lignin molecules can promote non-radiative migration and trigger photothermal conversion. So far, there are few studies on the conversion of lignin into photothermal materials in solar interfacial evaporation systems. The addition of lignin increases the pore size and hydrophilicity of the aerogel because lignin has abundant hydrophilic groups; the hydrophilic groups on the aerogel network can also reduce the evaporation enthalpy and achieve excellent evaporation performance. Therefore, the present invention combines the photothermal properties and structural adjustability of lignin, and proposes a cellulose / phenolic lignin-Fe aerogel and a cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel prepared based on the aerogel. Summary of the invention

[0005] In order to solve the problems in the prior art, the present invention provides a cellulose / phenolic lignin-Fe aerogel and a preparation method and application thereof. Specifically, the present invention uses phenolic lignin-Fe as a photothermal conversion material and changes its mass to regulate the aperture morphology of the solar evaporator. The phenolic lignin-Fe is compounded with the photocatalyst BiOBr, which can be simultaneously applied to solar seawater desalination and organic pollutant degradation.

[0006] To achieve the above object, the present invention proposes the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing cellulose / phenolic lignin-Fe aerogel, the method comprising the following steps:

[0008] S1: dispersing phenolic lignin-Fe powder in TEMPO oxidized cellulose nanofiber suspension to obtain a mixed solution, stirring the solution evenly, and standing the solution to obtain a cellulose / phenolic lignin-Fe composite hydrogel;

[0009] S2: The hydrogel is directionally frozen in a liquid nitrogen environment and vacuum dried to obtain a cellulose / phenolic lignin-Fe composite aerogel.

[0010] Furthermore, in the TEMPO oxidized cellulose nanofiber suspension described in S1, the solid content of the TEMPO oxidized cellulose is 2 to 2.5 wt.%;

[0011] The mass ratio of Tempo oxidized cellulose and phenolic lignin-Fe powder in the TEMPO oxidized cellulose nanofiber suspension is: (0.04-0.05): (0.08-0.1);

[0012] The temperature of the directional freezing in S2 is -196°C, the temperature of the vacuum freeze drying is -56 to -60°C, and the drying time is 12 to 24 hours.

[0013] Furthermore, the preparation method of phenolized lignin-Fe described in S1 comprises the following steps:

[0014] (1) dissolving lignin in phenol, adding sulfuric acid solution as a catalyst to the system, heating and stirring at 120° C. to obtain a lignin-phenol system; after the reaction is completed and cooled to room temperature, dissolving the lignin-phenol system in acetone-water solution, and dissolving the mixture in sulfuric acid solution, standing and precipitating; then centrifuging, washing, and freeze-drying to obtain phenolized lignin;

[0015] (2) Phenolated lignin and FeCl3·6H2O were dissolved in deionized water, and NaOH was added to adjust the pH to 12 to obtain a phenolated lignin-Fe system, and the solution was stirred at room temperature until it turned black; the precipitated powder obtained by centrifugation was washed with water until it was neutral, and freeze-dried to obtain phenolated lignin-Fe.

[0016] Furthermore, in step (1), the mass ratio of lignin to phenol is: (5-7): (10-15); the volume ratio of acetone to water in the acetone-water solution is: 9:1; the mass ratio of phenolized lignin to FeCl3·6H2O in step (2) is (0.1-0.2): (0.3-1), and the concentration of phenolized lignin in ionized water is 10-20wt%.

[0017] Furthermore, the method for preparing the TEMPO oxidized cellulose nanofiber suspension described in S1 comprises the following steps:

[0018] (1) adding TEMPO and NaBr to deionized water and stirring continuously to obtain a TEMPO-NaBr reaction system; dispersing cellulose in the TEMPO-NaBr reaction system until TEMPO and NaBr are completely dissolved and cellulose is fully dispersed, adding NaClO solution to adjust the pH value of the reaction system to 10-11, and slowly dripping 0.5M NaOH into the reaction system for 6-7 hours to maintain the pH value of the reaction system at 10-11;

[0019] Preferably, the cellulose length is >1 μm;

[0020] (2) After the reaction is completed, the obtained product is dispersed in deionized water and washed until neutral to obtain a TEMPO oxidized cellulose suspension; the TEMPO oxidized cellulose suspension is placed in an ice water bath for ultrasonic treatment to obtain a TEMPO oxidized cellulose nanofiber suspension.

[0021] Furthermore, in (1), the mass ratio of cellulose, TEMPO and NaBr is (1.5-2.5), (0.02-0.04): (0.2-0.4), and the total solid content of Tempo and NaBr in the TEMPO-NaBr reaction system is 0.08-0.2wt%.

[0022] The second object of the present invention is to provide a cellulose / phenolic lignin-Fe aerogel prepared by the above-mentioned preparation method.

[0023] The third object of the present invention is to provide the application of the above-mentioned cellulose / phenolic lignin-Fe aerogel in solar-driven seawater desalination.

[0024] The fourth object of the present invention is to provide a method for preparing a cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel, the method comprising the following steps:

[0025] S1: dispersing phenolic lignin-Fe powder and BiOBr-phenolic lignin-Fe powder in TEMPO oxidized cellulose nanofiber suspension to obtain a mixed solution, stirring the solution evenly and standing the solution to obtain a cellulose / phenolic lignin-Fe / BiOBr composite hydrogel;

[0026] S2: The hydrogel is directionally frozen in a liquid nitrogen environment and vacuum dried to obtain a cellulose / phenolic lignin-Fe / BiOBr composite aerogel.

[0027] Preferably, the temperature of directional freezing of the composite aerogel is -196°C, the temperature of vacuum freeze drying is -56 to -60°C, and the drying time is 12 to 24 hours.

[0028] Furthermore, in the TEMPO oxidized cellulose nanofiber suspension described in S1, the solid content of the TEMPO oxidized cellulose is 2 to 2.5 wt.%;

[0029] The mass ratios of Tempo oxidized cellulose, phenolic lignin-Fe, and BiOBr-phenolic lignin-Fe in the TEMPO oxidized cellulose nanofiber suspension are: (0.04-0.05): (0.08-0.1): (0.02-0.05).

[0030] Furthermore, the preparation method of BiOBr-phenolated lignin-Fe described in S1 comprises the following steps:

[0031] KBr and Bi(NO3)3·5H2O are sequentially added to an ethylene glycol solution and stirred until completely dissolved to obtain a BiOBr precursor solution; phenolated lignin-Fe powder is added to the BiOBr precursor solution and stirred until there are no particles, and a solvothermal reaction is carried out. After the reaction is completed, the precipitate is collected, and the precipitate is washed with anhydrous ethanol and deionized water respectively, and dried to obtain BiOBr / phenolated lignin-Fe.

[0032] Furthermore, the mass ratio of KBr, Bi(NO3)3·5H2O, phenolic lignin-Fe and ethylene glycol solution is: (0.1-0.5): (0.8-1): (0.03-0.08): (20-30).

[0033] The fifth object of the present invention is to provide a cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel, wherein the cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel is prepared by the above-mentioned preparation method.

[0034] The sixth object of the present invention is to provide the use of the aforementioned cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel in solar-driven seawater desalination and / or photocatalytic degradation of dye wastewater treatment.

[0035] In a particular embodiment, the wastewater is wastewater containing organic dyes; in some implementation scenarios, the main pollutant in the organic dye wastewater is rhodamine B.

[0036] Furthermore, the cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel is used in a solar evaporator, wherein the photothermal material phenolic lignin-Fe in the solar evaporator also plays a role of cross-linking with cellulose in the aerogel;

[0037] Preferably, the BiOBr-phenolic lignin-Fe composite comprises BiOBr, phenolic lignin and Fe 3+ ;

[0038] The aerogel matrix includes TEMPO oxidized cellulose nanofibers, phenolic lignin-Fe and BiOBr-phenolic lignin-Fe;

[0039] The present invention reduces the excessive use of chemical components by leveraging the functional diversity of lignin. Lignin is one of the three main components in plant cell walls and is a natural aromatic polymer formed by three phenylpropane units connected by carbon-oxygen bonds and carbon-carbon bonds. Lignin is able to achieve π-π stacking due to its rich aromatic ring structure, aliphatic and aromatic hydroxyl groups, and quinone groups, and can perform non-radiative migration and induce photothermal conversion. After phenolization, lignin has a large number of phenolic hydroxyl groups, forming a strong π-π conjugated structure, which can effectively promote non-radiative migration to produce photothermal conversion, and is an excellent solar light absorption material. The present invention combines the phenolized lignin with a polyphenol structure and Fe 3+ Under alkaline conditions, the phenolic hydroxyl groups in the phenolic lignin react with Fe 3+ Form metal complexes. Fe 3+ Not only can it be excited by photons and undergo dd transitions in the inner d orbital, but it can also effectively reduce the band gap of the phenolic lignin network and synergize with the π-π conjugated structure to obtain a more powerful solar-thermal energy conversion capacity.

[0040] Among semiconductor photocatalysts, BiOBr has a suitable band gap (2.9 eV), strong oxidizing properties, and chemical stability under visible light. After combining with phenolic lignin-Fe, the light absorption capacity of the catalyst is enhanced. The π-π bonds of phenolic lignin will induce the migration of photogenerated electrons on the valence band (VB) to the conduction band (CB) of BiOBr, while part of the electrons are transferred to phenolic lignin-Fe and the holes (h+) remain on the conduction band, which promotes the effective separation of electron-hole pairs generated by photoluminescence, thereby improving the performance of the photocatalyst in the photocatalytic reaction. The photogenerated electrons combine with dissolved oxygen in water to generate superoxide radicals, and the holes (h+) react with -OH to generate hydroxyl radicals. Superoxide radicals and hydroxyl radicals can degrade the dye into water molecules.

[0041] The present invention utilizes the hydroxyl groups on the surface of phenolized lignin-Fe to cross-link with the hydroxyl groups and carboxyl groups on the surface of TEMPO oxidized cellulose nanofibers to form hydrogen bonds; at the same time, Fe 3+ It can form a composite cross-link with the hydroxyl and carboxyl groups of cellulose, thereby improving the mechanical properties of the resulting aerogel and forming a three-dimensional network porous structure aerogel. The composite aerogel has the special property of being hydrophilic but insoluble in water, and is used for the escape of water vapor in the process of seawater desalination. The BiOBr-phenolic lignin-Fe complex is used as a photocatalyst to participate in the construction of the aerogel network, and is fixed by the strong three-dimensional network structure and chemical bonding of the aerogel, participating in the photocatalytic degradation of Rhodamine B dye wastewater in the process of solar-driven seawater desalination.

[0042] The beneficial effects of the present invention are:

[0043] 1. The cellulose / phenolic lignin-Fe aerogel and cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel prepared by the present invention are all derived from biomass materials, which fully realizes the reuse of waste biomass and has low cost and environmental friendliness. Cellulose / phenolic lignin-Fe aerogel can be used for seawater desalination, and cellulose / phenolic lignin-Fe / BiOBr composite aerogel can be used for seawater desalination and photocatalytic degradation of dye wastewater. The three-dimensional network porous structure of the aerogel not only helps the escape of water vapor and enhances the water evaporation effect, but also helps to increase the adsorption performance of the material, so that the pollutants contained in the wastewater are more easily exposed to the BiOBr-phenolic lignin-Fe catalyst in the three-dimensional network structure, thereby improving the photocatalytic performance.

[0044] 2. Phenolated lignin-Fe has multiple functions in the two aerogels of the present invention: First, lignin has a unique aromatic skeleton that can achieve π-π stacking. After phenolation, lignin has a large number of phenolic hydroxyl groups, forming a strong π-π conjugated structure, which can effectively promote non-radiative migration to produce photothermal conversion and is an excellent solar light absorption material. 3+ The metal complex formed can not only be excited by photons and undergo dd transitions in the internal d orbital, but also effectively reduce the band gap of the phenolic lignin network and cooperate with the π-π conjugated structure to obtain a stronger photothermal conversion ability; secondly, the hydroxyl groups on the surface of phenolic lignin-Fe cross-link with the hydroxyl and carboxyl groups on the surface of TEMPO oxidized cellulose nanofibers to form hydrogen bonds. 3+ It can form composite cross-links with the hydroxyl and carboxyl groups of cellulose, thereby improving the mechanical properties of the resulting aerogel and forming a three-dimensional network porous structure aerogel; finally, after combining with phenolic lignin-Fe, the π-π bonds of phenolic lignin will induce the migration of photogenerated electrons on the valence band (VB) to the conduction band (CB) of BiOBr, while part of the electrons are transferred to phenolic lignin-Fe and the holes (h+) are retained on the conduction band, promoting the effective separation of electron-hole pairs generated by photoluminescence, thereby improving the performance of the photocatalyst in the photocatalytic reaction.

[0045] 3. The addition of TEMPO oxidized cellulose nanofibers can not only evenly disperse the photothermal materials and photocatalysts in the aerogel, but also increase the degree of cross-linking by providing more cross-linking sites through surface groups.

[0046] 4. The present invention is the first to prepare cellulose / phenolic lignin-Fe aerogel and cellulose / phenolic lignin-Fe / BiOBr composite aerogel, which can photocatalytically degrade pollutants in dye wastewater while driving seawater desalination with solar energy, providing a new way for the functional utilization of lignin.

[0047] 5. The present invention can change the light-to-heat conversion rate and water transfer rate during evaporation by changing the phenolic lignin-Fe content and regulating the pore structure of the cellulose / phenolic lignin-Fe aerogel, thereby achieving a lower water evaporation enthalpy and improving the efficiency of solar seawater desalination. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is the infrared spectrum of phenolic lignin-Fe prepared in Example 1;

[0049] Figure 2 is the UV-Vis-NIR spectrum of the phenolic lignin-Fe prepared in Example 1;

[0050] Figure 3 is a scanning electron microscope image of the cross section of the aerogel prepared in Example 1 and Comparative Examples 1-3;

[0051] Figure 4 is a scanning electron microscope image of the longitudinal section of the aerogel prepared in Example 1 and Comparative Examples 1-3;

[0052] Figure 5 is a scanning electron microscope image of the composite aerogel prepared in Example 2;

[0053] Figure 6 is a graph showing the change in water evaporation mass of aerogels of Example 1, Comparative Examples 1-3, and pure water;

[0054] Figure 7 is a graph showing the change in water evaporation mass of the composite aerogel and pure water of Example 2;

[0055] Figure 8 1 is a diagram showing the photocatalytic degradation effect of the composite aerogels of Example 2 and Comparative Example 4 on Rhodamine B;

[0056] Fig. 9 is the Na before and after desalination of the composite aerogel prepared in Example 2 + , K + Mg 2+ , Ca 2+ Ion concentration effect diagram; DETAILED DESCRIPTION

[0057] The present invention is further explained below with reference to the examples, but the examples do not limit the present invention in any form.

[0058] The abbreviations in the present invention mean:

[0059] L: Lignin

[0060] PL: phenolic lignin

[0061] PL-Fe: phenolic lignin and Fe 3+of metal-polyphenol complexes, namely phenolic lignin-Fe;

[0062] BiOBr-phenolated lignin-Fe: complex of bismuth oxybromide and phenolated lignin-Fe;

[0063] T / PL-Fe: cellulose / phenolic lignin-Fe aerogel;

[0064] T / PL-Fe / B: cellulose / phenolic lignin-Fe / BiOBr composite aerogel;

[0065] TEMPO: 2,2,6,6-tetramethylpiperidinyl oxide;

[0066] Cellulose: TEMPO oxidized cellulose nanofibers;

[0067] RhB: rhodamine B;

[0068] WHO: World Health Organization;

[0069] EPA: U.S. Environmental Protection Agency;

[0070] The cellulose used in the embodiment of the present invention comes from poplar wood powder, and the lignin is alkaline lignin.

[0071] Example 1

[0072] S1: Preparation of phenolic lignin-Fe:

[0073] (1) dissolving lignin in phenol at a mass ratio of 1:2, adding 10 ml of sulfuric acid solution as a catalyst to the system, heating and stirring at 120° C., and reacting for 20 min to obtain a lignin-phenol system;

[0074] (2) After the reaction is completed and cooled to room temperature, the lignin-phenol system is dissolved in an acetone-water solution (the volume ratio of acetone to water is 9:1), and the mixture is dissolved in a sulfuric acid solution (PH = 1) and allowed to stand for precipitation. The precipitated suspension is centrifuged at 5000 rpm for 5 minutes, washed with deionized water several times until the pH value of the supernatant is neutral, and freeze-dried at -60°C for 48 hours to obtain phenolic lignin.

[0075] (3) Phenolated lignin (0.1 g) and FeCl3·6H2O (0.4 g) were dissolved in 10 mL of deionized water, and NaOH was added to adjust the pH to 12 to obtain a phenolated lignin-Fe system. The reaction was stirred at room temperature for 30 min until the solution turned black. The suspension was centrifuged at 5000 rpm for 5 min and washed with deionized water several times until the pH value of the supernatant was neutral, and then freeze-dried at -60 °C for 48 h to obtain phenolated lignin-Fe.

[0076] S2: Preparation of TEMPO-oxidized cellulose nanofiber suspension:

[0077] (1) Extraction of cellulose from poplar wood powder by eutectic method: Weigh 27.926g of choline chloride, 25.212g of oxalic acid dihydrate and 12.414g of ethylene glycol, heat and stir in an oil bath at 80℃ for 3h to obtain a homogeneous and transparent eutectic mixture. Mix 2g of dried poplar wood powder (300 mesh) with 30g of the prepared eutectic solvent, heat and stir in an oil bath at 110℃ for 3.5h. Then transfer the reaction solution to a 500mL beaker, add 400mL of propanol aqueous solution (the volume ratio of propanol to water is 7:3), stir at room temperature for 5h, and finally vacuum filter, wash with propanol / water solution, and dry at 60℃ to obtain dry cellulose, the length of which is >1μm.

[0078] (2) Add 0.033 g of TEMPO and 0.33 g of NaBr to 400 mL of deionized water and stir continuously to obtain a TEMPO-NaBr reaction system. Add 2 g of the dry cellulose prepared above and disperse it in the reaction system until TEMPO and NaBr are completely dissolved. When the cellulose is fully dispersed, add 21.27 g of NaClO solution, adjust the pH value of the reaction system to 10, and slowly drip 0.5 M NaOH into the reaction system for 6-7 hours, maintaining the pH value of the reaction system at 10. After the reaction is completed, the obtained product is dispersed in deionized water, washed with deionized water for 3-5 times, and then ultrasonically treated at 300 W for 5 minutes to further disperse the TOCN in the water to obtain a TEMPO oxidized cellulose nanofiber suspension.

[0079] S3: Preparation of cellulose / phenolic lignin-Fe aerogel:

[0080] (1) 0.1 g of phenolized lignin-Fe powder was completely dispersed in 2 g of a 2.5 wt% TEMPO oxidized cellulose nanofiber suspension to obtain a cellulose / phenolized lignin-Fe mixed solution, wherein the mass ratio of the Tempo oxidized cellulose to the phenolized lignin-Fe powder in the mixed solution was 0.05:0.1.

[0081] (2) The mixed solution was poured into a mold and allowed to stand for 12 h to obtain a cellulose / phenolic lignin-Fe composite hydrogel. The hydrogel was placed on a copper rod in a liquid nitrogen environment to achieve directional freezing and freeze-dried at -60 °C to obtain a cellulose / phenolic lignin-Fe-2 composite aerogel (T / PL-Fe-2).

[0082] Example 2

[0083] Steps S1 and S2 are the same as those in Example 1;

[0084] S3: Preparation of BiOBr-phenolic lignin-Fe composite by solvothermal method:

[0085] (1) 0.238 g KBr and 0.971 g Bi(NO3)3·5H2O were added to 25 ml ethylene glycol (99.9%) solution in sequence, and the mixture was stirred until completely dissolved to obtain a BiOBr precursor solution; 0.0697 g phenolated lignin-Fe powder was added to the BiOBr precursor solution, and the mixture was stirred until no particles were formed to obtain a BiOBr-phenolated lignin-Fe precursor solution.

[0086] (2) The BiOBr-phenolated lignin-Fe precursor solution was transferred to a polytetrafluoroethylene-lined autoclave, heated at 160°C for 10 hours, cooled to room temperature, and the precipitate was taken out, washed several times with anhydrous ethanol and deionized water, and dried at 60°C for 12 hours to obtain a BiOBr-phenolated lignin-Fe complex.

[0087] S4: Preparation of cellulose / phenolic lignin-Fe / BiOBr aerogel:

[0088] (1) 0.1 g of phenolic lignin-Fe and 20 mg of BiOBr-phenolic lignin-Fe complex were completely dispersed in 2 g of TEMPO oxidized cellulose nanofiber suspension with a content of 2.5 wt% to obtain a cellulose / phenolic lignin-Fe mixed solution.

[0089] (2) The mixed solution was poured into a mold and allowed to stand for 12 hours to obtain a cellulose / phenolic lignin-Fe / BiOBr composite hydrogel. The hydrogel was placed on a copper rod in a liquid nitrogen environment to achieve directional freezing, and freeze-dried at -60°C to obtain a cellulose / phenolic lignin-Fe / BiOBr-1 composite aerogel.

[0090] Comparative Example 1

[0091] Steps S1 and S2 are the same as those in Example 1;

[0092] S3: Preparation of cellulose / phenolic lignin-Fe aerogel:

[0093] (1) 0.2 g of phenolized lignin-Fe powder was completely dispersed in 2 g of 2.5 wt% TEMPO oxidized cellulose nanofiber suspension to obtain a cellulose / phenolized lignin-Fe mixed solution, wherein the mass ratio of Tempo oxidized cellulose to phenolized lignin-Fe powder in the mixed solution was 0.05:0.2.

[0094] (2) The mixed solution was poured into a mold and allowed to stand for 12 hours to obtain a cellulose / phenolic lignin-Fe composite hydrogel. The hydrogel was placed on a copper rod in a liquid nitrogen environment to achieve directional freezing and freeze-dried at -60°C to obtain a cellulose / phenolic lignin-Fe-1 composite aerogel (T / PL-Fe-1).

[0095] Comparative Example 2

[0096] Steps S1 and S2 are the same as those in Example 1;

[0097] S3: (1) 25 mg of phenolized lignin-Fe was completely dispersed in 2 g of 2.5 wt% TEMPO oxidized cellulose nanofiber suspension to obtain a cellulose / phenolized lignin-Fe mixed solution, in which the mass ratio of Tempo oxidized cellulose to phenolized lignin-Fe powder was 0.05:0.025.

[0098] (2) The mixed solution was poured into a mold and allowed to stand for 12 hours to obtain a cellulose / phenolic lignin-Fe composite hydrogel. The hydrogel was placed on a copper rod in a liquid nitrogen environment to achieve directional freezing and freeze-dried at -60°C to obtain a cellulose / phenolic lignin-Fe-3 composite aerogel (T / PL-Fe-3).

[0099] Comparative Example 3

[0100] Steps S1 and S2 are the same as those in Example 1;

[0101] S3: (1) 5 mg of phenolized lignin-Fe was completely dispersed in 2 g of 2.5 wt% TEMPO oxidized cellulose nanofiber suspension to obtain a cellulose / phenolized lignin-Fe mixed solution, in which the mass ratio of Tempo oxidized cellulose to phenolized lignin-Fe powder was 0.05:0.005.

[0102] (2) The mixed solution was poured into a mold and allowed to stand for 12 hours to obtain a cellulose / phenolic lignin-Fe composite hydrogel. The hydrogel was placed on a copper rod in a liquid nitrogen environment to achieve directional freezing, and freeze-dried at -60°C to obtain a cellulose / phenolic lignin-Fe-4 composite aerogel (T / PL-Fe-4).

[0103] Comparative Example 4

[0104] Steps S1, S2, and S3 are the same as those in Example 2;

[0105] S4:

[0106] (1) 0.1 g of phenolic lignin-Fe and 20 mg of pure BiOBr were completely dispersed in 2 g of 2.5 wt% TEMPO-oxidized cellulose nanofiber suspension to obtain a cellulose / phenolic lignin-Fe mixed solution.

[0107] (2) The mixed solution was poured into a mold and allowed to stand for 12 hours to obtain a cellulose / phenolic lignin-Fe composite hydrogel. The hydrogel was placed on a copper rod in a liquid nitrogen environment to achieve directional freezing, and freeze-dried at -60°C to obtain a cellulose / phenolic lignin-Fe / BiOBr-2 composite aerogel.

[0108] Analysis and Application

[0109] 1. Analyze the preparation process of Example 1:

[0110] (1) The infrared spectra and UV-visible-near infrared spectra of lignin, phenolic lignin, and phenolic lignin-Fe in Example 1 were monitored to investigate the performance of phenolic lignin-Fe as a light absorbing material. Figure 1 As shown, compared with lignin, the peak intensities at 1716, 1604, 1512 and 1450 cm-1 were observed to increase in the FT-IR spectrum of phenolized lignin, which was caused by the stretching vibration of the aromatic hydrocarbon skeleton and the benzene ring in the CH vibration, indicating that more aromatic hydrocarbon rings were successfully introduced after phenolization modification. Two new significant absorption peaks appeared at 833 and 754 cm-1, which means that the α-hydroxyl group on the lignin side chain has undergone a nucleophilic substitution reaction with the ortho and / or para position of the phenolic ring. In the spectrum of phenolized lignin-Fe, the peaks of the aromatic skeleton stretching vibration and the phenolic hydroxyl group are slightly reduced and shifted, which is consistent with the reaction of the hydroxyl group in the phenolized lignin with Fe. 3+ The formation of metal complexes. Figure 2 As shown in the UV-Vis-NIR spectrum, the light absorption capacity of phenolized lignin is significantly improved compared to lignin. This is because lignin has a large number of phenolic hydroxyl groups after phenolization, thus forming a strong π-π conjugated structure. The light absorption rate of phenolized lignin-Fe is the highest, which is due to the phenolic hydroxyl groups and Fe 3+ The formation of a metal complex allows it to undergo dd transitions in the inner d orbital, synergizing with the π-π conjugated structure to achieve stronger photothermal conversion capabilities.

[0111] (2) The scanning electron microscopy images of cellulose / phenolic lignin-Fe aerogels 1, 2, 3, and 4 prepared in Example 1 and Comparative Examples 1-3 are shown in FIG. Figure 3ad (cross section), 4a-d (longitudinal section). Cellulose / phenolic lignin-Fe aerogel has an interconnected porous structure and forms a vertically grown directional frozen structure under liquid nitrogen conditions. It can be seen that the pore sizes of cellulose / phenolic lignin-Fe-1, cellulose / phenolic lignin-Fe-2, cellulose / phenolic lignin-Fe-3, and cellulose / phenolic lignin-Fe-4 are 39.427±18, 41.313±14, 56.656±22, and 61±20μm, respectively. With the increase of the content of phenolic lignin-Fe, the porous structure of the prepared aerogel becomes dense, indicating that the content of phenolic lignin-Fe can well adjust the microstructure of the obtained aerogel, making the pores of the aerogel relatively small. The difference in the pore structure of different cellulose / phenolic lignin-Fe aerogels is mainly due to the relatively high content of phenolic lignin-Fe hindering the growth of ice crystals, resulting in the formation of relatively small ice crystals in aerogels with low phenolic lignin-Fe content, thereby forming small pores.

[0112] (3) The scanning electron microscopy image of the cellulose / phenolic lignin-Fe / BiOBr aerogel prepared in Example 2 is as follows: Figure 5 a (cross section) and 5b (longitudinal section). It can be observed that BiOBr-phenolic lignin-Fe is successfully attached to the three-dimensional porous network of the aerogel. Compared with Example 1, BiOBr-phenolic lignin-Fe does not change the original microstructure of the cellulose / phenolic lignin-Fe aerogel, confirming the successful construction of the cellulose / phenolic lignin-Fe / BiOBr composite aerogel.

[0113] (4) The water evaporation performance of the aerogels prepared in Example 1 and Comparative Examples 1-3 is as follows Figure 6 As shown:

[0114] The composite aerogel was placed on the water surface under a xenon lamp simulating a light source of 1 sun, and the changes in water quality were recorded using an electronic balance. Figure 6 It can be seen that the cumulative mass change of water in different samples increases linearly with the increase of illumination time. According to the mass change curve, the evaporation rate was calculated. Under 1 simulated sunlight, as the concentration of phenolic lignin-Fe decreased, the water evaporation rates of T / PL-Fe-1, T / PL-Fe-2, T / PL-Fe-3 and T / PL-Fe-4 evaporators within 1 hour were 2.27, 2.64, 1.92 and 1.28 kgm, respectively. -2 , respectively pure water (0.37kgm -2 h -1) by 6.13, 7.13, 5.19 and 3.45 times, confirming the effective regulation of phenolic lignin-Fe on the performance of solar evaporator. Among them, T / PL-Fe-2 has the highest evaporation rate, which is due to the addition of phenolic lignin-Fe to adjust the pore size of the aerogel to a range that is conducive to water evaporation. With the increase of phenolic lignin-Fe content, the pore size of the aerogel decreases. The small-pore porous material can make the light reflect and refract multiple times when encountering the pore wall, thereby extending the light path and increasing the light absorption rate, converting solar energy into heat for water evaporation. At the same time, as a photothermal material, the increase in the content of phenolic lignin-Fe helps to increase the light absorption of the aerogel. In addition, the thermal conductivity of the evaporator decreases with the decrease in pore size, which is mainly due to the boundary effect caused by the increase in interfaces and smaller pores, which increases the thermal resistance, reduces heat transfer, and is conducive to heat localization. The reduction of phenolic lignin-Fe content will form a larger pore size. The large pore channel and high porosity enable the aerogel to achieve high-speed water transmission, so that the salt can be quickly redissolved in the water to inhibit salt accumulation, which is conducive to steam overflow. The high phenolic lignin-Fe content in T / PL-Fe-1 leads to small pores and easy clogging, which is not conducive to the rapid transmission of water in the aerogel, resulting in a reduced evaporation rate. However, T / PL-Fe-3 and T / PL-Fe-4 cannot achieve efficient photothermal conversion due to their low phenolic lignin-Fe content, and the large pores allow a large amount of water to be transported to the surface of the aerogel, resulting in a large heat loss, which leads to a reduced evaporation rate.

[0115] (5) The mass change of the cellulose / phenolic lignin-Fe / BiOBr composite aerogel prepared in Example 2 under one simulated sunlight is as follows: Figure 7 The cellulose / phenolic lignin-Fe / BiOBr composite aerogel can reach 2.31 kg m in 1 hour. -2 , which confirms that the addition of photocatalyst does not have a significant effect on the pore structure and water evaporation rate of the composite aerogel.

[0116] (6) The photocatalytic degradation effect of the composite aerogel in Example 2 is as follows Figure 8 As shown. First, in order to verify the performance of BiOBr-phenolated lignin-Fe composite as a photocatalyst, comparative example 4 with pure BiOBr as a photocatalyst was prepared under the same conditions. Under 1 sunlight, which is the same as the water evaporation conditions, the degradation effect of the composite aerogel on the dye Rhodamine B (20 mg / L) was investigated. During the photocatalytic reaction, 1 mL of Rhodamine B solution was taken every 30 minutes, and the absorbance at a wavelength of 554 nm was detected by a UV-visible spectrophotometer. The degradation efficiency of Rhodamine B is expressed as C / C0, where C0 and C represent the concentrations of Rhodamine B at the initial time and illumination time (minutes), respectively. Figure 6The photodegradation of RhB with different concentrations by composite aerogels changes with illumination time. It can be seen that compared with pure BiOBr, the composite aerogel with BiOBr-phenolic lignin-Fe as a photocatalyst exhibits a higher photodegradation efficiency, which can reach 81%. This is because the phenolic lignin-Fe enhances the light-harvesting ability of the catalyst, and the π-π bond of the phenolic lignin induces the migration of photogenerated electrons on the valence band (VB) to the conduction band (CB) of BiOBr, while part of the electrons are transferred to the phenolic lignin-Fe and the holes (h+) are retained in the conduction band, which promotes the effective separation of electron-hole pairs generated by photoluminescence, thereby improving the performance of the photocatalyst in the photocatalytic reaction.

[0117] (7) The cellulose / phenolic lignin-Fe / BiOBr composite aerogel prepared in Example 2 was desalinated. The Na + , K + Mg 2+ , Ca 2+ Effect of ion concentration Fig. 9 In order to estimate the actual desalination capacity of the composite aerogel, the Yellow Sea water was selected and the ion concentration before and after seawater desalination was measured by ICP-MS. In the desalination experiment, we collected and measured the Na + , K + Mg 2+ and Ca 2+ According to the ion concentration. Fig. 9 The results showed that the solar evaporator can significantly reduce the ion concentration in seawater by 3-4 orders of magnitude, far below the salinity level of drinking water specified by the WHO and the US Environmental Protection Agency. When converted into ion removal rate, the composite aerogel has a significant effect on Na + , K + Mg 2+ and Ca 2+ The interception rates were 99.99%, 99.94%, 99.99% and 99.90% respectively.

[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing cellulose / phenolic lignin-Fe aerogel, characterized in that: The method comprises the following steps: S1: dispersing phenolic lignin-Fe powder in TEMPO oxidized cellulose nanofiber suspension to obtain a mixed solution, stirring it evenly, and standing it to obtain a cellulose / phenolic lignin-Fe composite hydrogel; the mass ratio of TEMPO oxidized cellulose to phenolic lignin-Fe powder is: (0.04-0.05): (0.08-0.1); S2: Directionally freeze the hydrogel in a liquid nitrogen environment and vacuum dry it to obtain a cellulose / phenolic lignin-Fe composite aerogel; The preparation method of phenolized lignin-Fe described in S1 comprises the following steps: (1) dissolving lignin in phenol, adding sulfuric acid solution as a catalyst to the system, heating and stirring at 120°C to obtain a lignin-phenol system; after the reaction is completed and cooled to room temperature, dissolving the lignin-phenol system in acetone-water solution, and dissolving the mixture in sulfuric acid solution, standing and precipitating; then centrifuging, washing, and freeze-drying to obtain phenolic lignin; (2) Phenolated lignin and FeCl3∙6H2O were dissolved in deionized water, and NaOH was added to adjust the pH to 12 to obtain a phenolated lignin-Fe system. The solution was stirred at room temperature until it turned black. The precipitated powder obtained by centrifugation was washed with water until it was neutral, and freeze-dried to obtain phenolated lignin-Fe.

2. The preparation method according to claim 1, characterized in that: In the TEMPO oxidized cellulose nanofiber suspension described in S1, the solid content of the TEMPO oxidized cellulose is 2-2.5wt.%; The temperature of the directional freezing in S2 is -196°C, the temperature of the vacuum drying is -56~-60°C, and the drying time is 12-24 hours.

3. The preparation method according to claim 1, characterized in that: The mass ratio of lignin to phenol in step (1) is: (5-7): (10-15); the volume ratio of acetone to water in the acetone-water solution is 9:1; the mass ratio of phenolized lignin to FeCl3∙6H2O in step (2) is (0.1-0.2): (0.3-1), and the concentration of phenolized lignin in ionized water is 10-20wt%.

4. The preparation method according to claim 1, characterized in that: The method for preparing the TEMPO oxidized cellulose nanofiber suspension described in S1 comprises the following steps: (1) Add TEMPO and NaBr to deionized water and stir continuously to obtain a TEMPO-NaBr reaction system; disperse cellulose in the TEMPO-NaBr reaction system until TEMPO and NaBr are completely dissolved and cellulose is fully dispersed, add NaClO solution to adjust the pH value of the reaction system to 10-11, and slowly drip 0.5M NaOH into the reaction system for 6-7 hours to maintain the pH value of the reaction system at 10-11; (2) After the reaction is completed, the obtained product is dispersed in deionized water and washed until neutral to obtain a TEMPO oxidized cellulose suspension; the TEMPO oxidized cellulose suspension is placed in an ice water bath for ultrasonic treatment to obtain a TEMPO oxidized cellulose nanofiber suspension.

5. The preparation method according to claim 4, characterized in that: (1), the cellulose length is >1 μm.

6. The preparation method according to claim 4, characterized in that: In (1), the mass ratio of cellulose, TEMPO and NaBr is (1.5-2.5), (0.02-0.04): (0.2-0.4), and the total solid content of Tempo and NaBr in the TEMPO-NaBr reaction system is 0.08-0.2wt%.

7. A cellulose / phenolic lignin-Fe aerogel, characterized in that: The preparation method according to claim 1 is used for preparation.

8. Use of the cellulose / phenolic lignin-Fe aerogel according to claim 7 in solar-driven seawater desalination.

9. A method for preparing a cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel, characterized in that: The method comprises the following steps: S1: dispersing phenolic lignin-Fe powder and BiOBr-phenolic lignin-Fe powder in TEMPO oxidized cellulose nanofiber suspension to obtain a mixed solution, stirring evenly, and standing to obtain a cellulose / phenolic lignin-Fe / BiOBr composite hydrogel; the mass ratio of TEMPO oxidized cellulose, phenolic lignin-Fe, and BiOBr-phenolic lignin-Fe is (0.04-0.05): (0.08-0.1): (0.02-0.05); S2: Directionally freeze the hydrogel in a liquid nitrogen environment and vacuum dry it to obtain a cellulose / phenolic lignin-Fe / BiOBr composite aerogel; The preparation method of phenolized lignin-Fe described in S1 comprises the following steps: (1) dissolving lignin in phenol, adding sulfuric acid solution as a catalyst to the system, heating and stirring at 120°C to obtain a lignin-phenol system; after the reaction is completed and cooled to room temperature, dissolving the lignin-phenol system in acetone-water solution, and dissolving the mixture in sulfuric acid solution, standing and precipitating; then centrifuging, washing, and freeze-drying to obtain phenolic lignin; (2) dissolving phenolic lignin and FeCl3∙6H2O in deionized water, and adding NaOH to adjust the pH to 12 to obtain a phenolic lignin-Fe system, and stirring at room temperature until the solution turns black; washing the precipitated powder obtained by centrifugation with water until it is neutral, and freeze-drying to obtain phenolic lignin-Fe; The preparation method of BiOBr-phenolated lignin-Fe described in S1 comprises the following steps: KBr and Bi(NO3)3·5H2O are sequentially added to an ethylene glycol solution and stirred until completely dissolved to obtain a BiOBr precursor solution; phenolated lignin-Fe powder is added to the BiOBr precursor solution and stirred until there are no particles, and a solvothermal reaction is carried out. After the reaction is completed, the precipitate is collected, and the precipitate is washed with anhydrous ethanol and deionized water respectively, and dried to obtain BiOBr / phenolated lignin-Fe.

10. The preparation method according to claim 9, characterized in that: In the TEMPO oxidized cellulose nanofiber suspension described in S1, the solid content of Tempo oxidized cellulose is 2~2.5wt.%.

11. The preparation method according to claim 9, characterized in that: The mass ratio of KBr, Bi(NO3)3·5H2O, phenolic lignin-Fe and ethylene glycol solution is: (0.1-0.5): (0.8-1): (0.03-0.08): (20-30).

12. A cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel, characterized in that: The cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel is prepared by the preparation method described in claim 9.

13. Use of the cellulose / phenolic lignin-Fe / BiOBr composite bifunctional aerogel according to claim 12 in solar-driven seawater desalination and / or photocatalytic degradation of dye wastewater treatment.

Citation Information

Patent Citations

  • Preparation method of cellulose / BiOBr composite photocatalytic material

    CN108355717A

  • Biomass aerogel-based seawater evaporator with controllable aperture and preparation method thereof

    CN116426028A